PROTOTYPE ALAT PEMBERIAN PAKAN AYAM OTOMATIS MENGGUNAKAN ARDUINO DAN INTERNET OF THINGS UNTUK NOTIFIKASI KETERSEDIAAN PAKAN - Ahmad Rufa’i; Zakaria Ansori (Journal of Innovation And Future Technology (IFTECH), 2022)
In this modern era, we as a society need to take advantage of Technology to supPort chicken breeding activities, especially in the field of animal husbandry. One of the potential farms is broiler chickens. Broiler chickens are a type of poultry that produces meat. One of the factors of accelerating the growth of broiler chickens can also be measured from regular and systematic feeding, scheduling of feeding. At this time the food filling system in raising chickens still uses manual, namely using human labor, therefore the management of the automatic feeding system will be more efficient in maintaining broiler chickens and make it easier for farm owners to control the stock of feed availability. In conducting this research, the type of research used is a qualitative data collection method. In addition, the system that will be built uses the Waterfall design method. In modeling this application using the UML method in the form of use case diagrams, class diagrams, activity diagrams, and squence diagrams. The result of this research is the production of an automaticchicken feed prototype using Arduino and the Internet of Things for feed availability notification.